"Life's Simple 7" and Long‐Term Mortality After Stroke. Issue 11 (20th November 2015) - Lin, Michelle P.; Ovbiagele, Bruce; Markovic, Daniela; Towfighi, Amytis
Abstract : Background: The American Heart Association developed criteria dubbed "Life's Simple 7" defining ideal cardiovascular health: not smoking, regular physical activity, healthy diet, maintaining normal weight, and controlling cholesterol, blood pressure, and blood glucose levels. The impact of achieving these metrics on survival after stroke is unknown. We aimed to determine cardiovascular health scores among stroke survivors in the United States and to assess the link between cardiovascular health score and all‐cause mortality after stroke. Methods and Results: We assessed cardiovascular health metrics among a nationally representative sample of US adults with stroke (n=420) who participated in the National Health and Nutrition Examination Surveys in 1988–1994 (with mortality assessment through 2006). We determined cumulative all‐cause mortality by cardiovascular health score under the Cox proportional hazards model after adjusting for sociodemographic characteristics and comorbidities. No stroke survivors met all 7 ideal health metrics. Over a median duration of 98 months (range, 53–159), there was an inverse dose‐dependent relationship between number of ideal lifestyle metrics met and 10‐year adjusted mortality: 0 to 1: 57%; 2: 48%; 3: 43%; 4: 36%; and ≥5: 30%. Those who met ≥4 health metrics had lower all‐cause mortality than those who met 0 to 1 (hazard ratio, 0.51; 95% confidence interval, 0.28–0.92). After adjusting for sociodemographics, higher health score was associated with lower all‐cause mortality (trend P ‐value, 0.022). Conclusions: Achieving a greater number of ideal cardiovascular health metrics is associated with lower long‐term risk of dying after stroke. Specifically targeting "Life's Simple 7" goals might have a profound impact, extending survival after stroke.